The Relationship Of Elderly Knowledge And Family Support To The Extent Of Activation Of Older People In The Workplace Village Of Baidub Ulilin District Merauke - Efrida Lanto'e; Nita Dwi Astikasari; Erma Retnaningtyas; Tety Ripursari (Universitas STRADA Indonesia, 2024)
Old age (elderly) can be said to be the final stage of human life development. The efforts needed to solve problems and empower the elderly are promotive, preventive, curative and rehabilitative. Posyandu for the elderly is a program provided by the government, especially the Health Service, which is then coordinated by the community health center in each sub-district and then managed and organized by community social service organizations or groups. The low coverage of posyandu services for the elderly in Baidub village in the Ulilin health center area is caused by several factors. The aim of this research is to analyze the relationship between knowledge of the elderly and family support on the range of activities of the elderly. The type of research used in this research is analytical observational with a cross sectional design. Data processing and analysis was carried out univariate and bivariate. The collection technique was simple random sampling with a sample size of 41 respondents. Location and time of research at the Baidub posyandu in the working area of ​​the Ulilin health center in February 2024. The research results showed that of the 41 respondents, the majority of elderly people in Baidub village were elderly and young elderly (78%) with the highest level of education, namely elementary school (63%). Then from the level of knowledge about posyandu it can be said that it is not good because the results show that the elderly have a sufficient level of knowledge (32%) and less knowledge (36%). Likewise, family support is still said to be lacking because research results show that family support is lacking (56%). This causes the elderly to be less active in going to the Posyandu for the elderly, with research results showing that the number of elderly people going to the posyandu is less or not active (56%).The significant relationship between knowledge of the elderly and the activity of the elderly in going to Posyandu can be seen from the calculation results Chi Square with Contingency Correlation Coefficient analysis found a result of 0.45 with a significance level of a = 0.05. Meanwhile, the significant relationship between family support and elderly activity at the posyandu can be seen from the results of the Chi Square calculation and contingency analysis coefficient with a result of 0.64 with a significance level of a = 0.05. Conclusion: From the research results, it can be concluded that there is a significant relationship between knowledge of the elderly and family support and the activity of the elderly at the elderly posyandu in Baidub Village in the working area of ​​the Ulilin Community Health Center, Merauke district.